محرمات الطعام والشراب في القرآن الكريم وأثرها في حفظ صحة الإنسان في الحضارة الإسلامية - Abu Zeid, Mohamed (Jurnal Studi Al-Qur’an, 2020)
What was deprived of food and drink it was harmful to a person’s health or himself. In this research, the researcher deals with the prohibitions of food and drink in the Holy Quran, as it explains how the ban of these beverages had a definite impact on the Islamic nation in the best conditions of physical and psychological health. This research will solve according to the inductive and descriptive approach, whereby the researcher will extrapolate the Quranic text and determine the prohibitions of foods and beverages in it, whether they are specific or outlined in the Quranic texts such as the prohibition of malice. The researcher will transfer the findings of Sharia scholars or natural sciences scientists from the harms of those taboos And its mental, psychological, and physical effects. He described the impact of the purity of Islamic society on these taboos on the development and advancement of Islamic civilization